First-time detection and identification of the Mycobacterium tuberculosis Complex members in extrapulmonary tuberculosis clinical samples in south Tunisia by a single tube tetraplex real-time PCR assay - Siala, Mariam; Smaoui, Salma; Taktak, Wafa; Hachicha, Salma; Ghorbel, Asma; Marouane, Chema; Kammoun, Sana; Gamara, Dhikrayet; Slim, Leila; Gdoura, Radhouane; Messadi-Akrout, Férièle (PLoS neglected tropical diseases, 2017)
Tunisia has one of the highest burdens of extrapulmonary tuberculosis (EPTB) among tuberculosis (TB) cases but the contribution of MTBC-mediated human EPTB is unknown. EPTB diagnosis is challenging due to the paucibacillary nature of clinical samples. Therefore, a need of a simplified molecular method for sensitive and specific TB detection and differentiation of MTBC members caused EPTB remains a priority to an early diagnosis, optimize successful anti-TB treatment and minimize transmission. We evaluated the performance of a single tube tetraplex Taq Man real time PCR for EPTB detection and differentiation between MTBC members directly on extrapulmonary samples. Extrapulmonary samples obtained from clinically suspected EPTB patients from 2013 to April 2015 were tested by Ziehl Neelsen Staining, mycobacterial culture and qPCR assay for RD1, RD9, RD12 and ext-RD9 targets (MTBC-RD qPCR). The performance of qPCR was compared to a reference standard based on MTBC culture and/or at least two criteria of a composite reference standard (CRS) including clinical, radiological, histopathological and therapeutic findings. EPTB was identified in 157/170 (92.4%) of included patients of whom 99 (63%) were confirmed by culture and 58 (36.9%) by CRS criteria. The sensitivity and specificity of qPCR, in comparison to the reference standard were 100% (157/157) and 92.3% (12/13), respectively. The sensitivity of qPCR was statistically significant as compared to culture and smear microscopy (P< 0.001). QPCR results showed M. bovis identification in 77.1% of extrapulmonary samples in occurrence to lymphadenitis infection. M. tuberculosis and M.bovis BCG were detected in 21.6% and 1.3% of cases, respectively. MTBC-RD qPCR proved to be a rapid and sensitive assay for simultaneously TB detection and MTBC members identification on extrapulmonary samples within 1.5 days after sample receipt. Its high sensitivity could make this method a useful tool in diagnosing TB in addition to routine conventional methods and TB clinical parameters.